A Principled Relation between Reading and Naming in Acquired and Developmental Anomia: Surface Dyslexia Following Impairment in the Phonological Output Lexicon - Gvion, Aviah; Friedmann, Naama (Frontiers in Psychology, 2016)
Lexical retrieval and reading aloud are often viewed as two separate processes. However, they are not completely separate--they share components.This study assessed the effect of an impairment in a shared component, the phonological output lexicon,on lexical retrieval and on reading aloud. Because the phonological output lexicon is part of the lexical route for reading, individuals with an impairment in this lexicon may be forced to read aloud via the sublexical route and therefore show a reading pattern that is typical of surface dyslexia. To examine the effect of phonological output lexicon deficit on reading, we tested the reading of 16 Hebrew-speaking individuals with phonological output lexicon anomia, 8 with acquired anomia following brain damage and 8 with developmental-anomia.We established that they had a phonological output lexicon deficit according to the types of errors and the effects on their naming in a picture naming task, and excluded other deficit loci in the lexical retrieval process according to a line of tests assessing their picture and word comprehension, word and nonword repetition, and phonological working memory. After we have established that the participants have a phonological output lexicon deficit, we tested their reading. To assess their reading and type of reading impairment, we tested their reading aloud, lexical decision, and written word comprehension. We found that all of the participants with phonological output lexicon impairment showed, in addition to anomia, also the typical surface dyslexia errors in reading aloud of irregular words,words with ambiguous conversion to phonemes,and potentiophones (words like "now" that, when read via the sublexical-route,can be sounded out as another word, "know"). Importantly, all the participants performed flawlessly on pseudohomophone lexical-decision and on homophone/potentiophone reading comprehension, indicating spared orthographic-input-lexicon and spared access to it and from it to lexical semantics. This pattern was shown both by the adults with acquired anomia and by the participants with developmental anomia. These results thus suggest a principled relation between anomia and dyslexia, and point to a distinct type of surface dyslexia. They further show the possibility of good comprehension of written words when the phonological output stages are impaired.